1990
DOI: 10.1093/ajcn/52.5.872
|View full text |Cite
|
Sign up to set email alerts
|

Mother-daughter pairs: spinal and femoral bone densities and dietary intakes

Abstract: Bone mineral density (BMD) of the lumbar spine (L1-L4) and femur (femoral neck, Ward's triangle, and trochanter) was measured in 37 healthy, white mother-daughter pairs by dual-photon absorptiometry. Mothers and daughters were aged 52 +/- 7 and 25 +/- 4 y (mean +/- SD), respectively. Three-day dietary intakes were evaluated. Significant correlations between mother-daughter pairs for BMD of all lumbar and femoral areas [except for L2 (r = 0.26, P = 0.054)] indicated familial resemblances in bone mineralization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 26 publications
(8 reference statements)
2
40
0
Order By: Relevance
“…We observed significant motherdaughter correlations in BMD, consistent with other parent-offspring studies, (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) which did not change substantially with adjustment for potential covariates, such as age and anthropometry. Daughters, particularly premenopausal daughters, of mothers with ''normal BMD'' had greater BMD at all sites than daughters of mothers who had established osteoporosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We observed significant motherdaughter correlations in BMD, consistent with other parent-offspring studies, (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) which did not change substantially with adjustment for potential covariates, such as age and anthropometry. Daughters, particularly premenopausal daughters, of mothers with ''normal BMD'' had greater BMD at all sites than daughters of mothers who had established osteoporosis.…”
Section: Discussionsupporting
confidence: 89%
“…Low bone mass is associated with increased risk of fracture but is considered a necessary, not a sufficient, predisposing factor. (3) Previous studies have reported significant and relatively consistent parent-offspring correlations in bone mineral density (BMD) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and have shown that a family history of osteoporosis and/or fracture is associated with an increased risk of low BMD and fracture. (14)(15)(16)(17)(18)(19) Some, (14,16) but not all, (6,13,(17)(18)(19) of these studies confirmed a family history of osteoporosis or fracture via medical records or radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…Bone mass has a very strong genetic component: twin and family studies reveal that 50 to 90% of the variance in BMD is caused by genetic factors (Pocock et al 1987;Slemenda et al 1991;Lutz & Tesar, 1990;Gueguen et al 1995;Hunter et al 2001). Whole genome-wide linkage studies (Wilson et al 2003;Devoto et al 1998;Kammerer et al 2003;Karasik et al 2004;Ralston et al 2005) have been launched to search for genes underlying BMD variation.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the growth period, a large variance in bone mineral density (BMD) 1 and content (BMC), in either the axial or the appendicular skeleton, is observed both in healthy females and males (4)(5)(6)(7)(8). Many genetic and environmental factors have been suggested to influence bone mass accumulation during this period (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%